Development of biocomposites from cotton fiber reinforced albumen - Yusliza binti Yusof (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Currently, engineering are being integrated to provide the impetus for new materials and products that are compatible with the environment and independent of fossil fuels. In order to suit with the environmental friendly issues and global need, this study was designed in such that the focus will be on the development of biocomposites from cotton fiber reinforced albumen (egg white). Hand lay-up technique was selected to fabricate the cotton/albumen composites (CAC) before it was cured at room temperature. The composite systems were studied on the effect of three variables: fiber content, curing time and pH-adjusted albumen. The composites density, tensile and impact testing were carried out to evaluate the physical and mechanical properties of the fabricated composites. The composite structures, functional chemical groups and thermal stability were characterized by XRD, FTIR and TGA analysis, respectively. The fiber content in the CAC was varied from 0 to 16% w/w. As expected, the incorporation of cotton fibers produces a substantial increase in terms of strength and toughness. The maximum tensile strength of 8 MPa and impact strength of 18.0 kJ/m2, respectively, was found in the CAC with 10% w/w of fiber content. The results show that cotton fibers could provide effective reinforcement with albumen due to its morphological and mechanical properties. It was also observed that with the increased of curing time at room temperature from 7 to 21 days, there was substantial increment in the mechanical properties of the CAC. The strength of the CAC however, remains constant after 21 days. The curing process was crucial to ensure good strength and stiffness of the fibers. On the addition of acetic acid (CH3COOH) and sodium hydroxide (NaOH) would further denature the albumen, and thereby its pH values were adjusted from pH 5 to 11. The mechanical properties of the CAC increasing as the pH albumen increased and the results were optimized at pH 9. The morphology examination using SEM justify the experimental results obtained for all factors mentioned, which always correlates to the intrinsic adhesion of the fiber/matrix interface. Thus, the utilization of CAC is discussed as new thermosetting biocomposites, which has great potential as the alternative to petroleum based materials for specific building applications with minor strength requirements.